Vapor pressure of aqueous solutions of electrolytes reproduced with coarse-grained models without electrostatics - Pérez Sirkin, Yamila Anahí (2016)
The vapor pressure of water is a key property in a large class of applications from the design of membranes for fuel cells and separations to the prediction of the mixing state of atmospheric aerosols. Molecular simulations have been used to compute vapor pressures, and a few studies on liquid mixtures and solutions have been reported on the basis of the Gibbs Ensemble Monte Carlo method in combination with atomistic force fields. These simulations are costly, making them impractical for the prediction of the vapor pressure of complex materials. The goal of the present work is twofold: (1) to demonstrate the use of the grand canonical screening approach (Factorovich, M. H. et al. J. Chem. Phys. 2014, 140, 064111) to compute the vapor pressure of solutions and to extend the methodology for the treatment of systems without a liquid−vapor interface and (2) to investigate the ability of computationally efficient high-resolution coarse-grained models based on the mW monatomic water potential and ions described exclusively with short-range interactions to reproduce the relative vapor pressure of aqueous solutions. We find that coarse-grained models of LiCl and NaCl solutions faithfully reproduce the experimental relative pressures up to high salt concentrations, despite the inability of these models to predict cohesive energies of the solutions or the salts. A thermodynamic analysis reveals that the coarse-grained models achieve the experimental activity coefficients of water in solution through a compensation of severely underestimated hydration and vaporization free energies of the salts. Our results suggest that coarse-grained models developed to replicate the hydration structure and the effective ion−ion attraction in solution may lead to this compensation. Moreover, they suggest an avenue for the design of coarse-grained models that accurately reproduce the activity coefficients of solutions.